PENGARUH PERSENTASE KATALIS TERHADAP SIFAT MEKANIS KOMPOSIT BERMATRIK RESIN POLYESTER - Ade Sieva Perwara (Approach : Jurnal Teknologi Penerbangan, 2021)
Composite is a combination of two or more materials so as to provide better properties than the constituent materials. The composite was made using 90% Yukalac C-108 B Justus Polyester Resin, with a mixture of 1%, 2% and 3% MEPOXE catalyst, and the fiber used was fiberglass with 10% woven fiber orientation, and dried at room temperature for 1x24 hours. When the specimen is completely dry, the specimen will be shaped according to the specified standard, for the tensile test specimen it is made according to the ASTM D638 standard while the impact test specimen is according to the ASTM A370 standard. The tensile test showed that the highest average tensile strength was obtained from the percentage of 3% catalyst, and the highest average strain was from the percentage of 2% catalyst. In the impact test, the highest average fracture resistance and ductility values were obtained from specimens with a catalyst percentage of 3%, and the lowest was 1%.